oriC-encoded instructions for the initiation of bacterial chromosome replication - Wolański, Marcin; Donczew, Rafał; Zawilak-Pawlik, Anna; Zakrzewska-Czerwińska, Jolanta (Frontiers in Microbiology, 2015)
Replication of the bacterial chromosome initiates at a single origin of replication that is called oriC. This occurs via the concerted action of numerous proteins, including DnaA, which acts as an initiator. The origin sequences vary across species, but all bacterial oriCs contain the information necessary to guide assembly of the DnaA protein complex at oriC, triggering the unwinding of DNA and the beginning of replication. The requisite information is encoded in the unique arrangement of specific sequences called DnaA boxes, which form a framework for DnaA binding and assembly. Other crucial sequences of bacterial origin include DNA unwinding element (DUE, which designates the site at which oriC melts under the influence of DnaA) and binding sites for additional proteins that positively or negatively regulate the initiation process. In this review, we summarize our current knowledge and understanding of the information encoded in bacterial origins of chromosomal replication, particularly in the context of replication initiation and its regulation. We show that oriC encoded instructions allow not only for initiation but also for precise regulation of replication initiation and coordination of chromosomal replication with the cell cycle (also in response to environmental signals). We focus on E. coli, and then expand our discussion to include several other microorganisms in which additional regulatory proteins have been recently shown to be involved in coordinating replication initiation to other cellular processes (e.g., Bacillus, Caulobacter, Helicobacter, Mycobacterium, and Streptomyces). We discuss diversity of bacterial oriC regions with the main focus on roles of individual DNA recognition sequences at oriC in binding the initiator and regulatory proteins as well as the overall impact of these proteins on the formation of initiation complex.